2010
DOI: 10.1128/aac.00148-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Genotypic Prediction of HIV-1 Coreceptor Use versus a Phenotypic Assay and Correlation with the Virological Response to Maraviroc: the ANRS GenoTropism Study

Abstract: Genotypic algorithms for prediction of HIV-1 coreceptor usage need to be evaluated in a clinical setting. We aimed at studying (i) the correlation of genotypic prediction of coreceptor use in comparison with a phenotypic assay and (ii) the relationship between genotypic prediction of coreceptor use at baseline and the virological response (VR) to a therapy including maraviroc (MVC). Antiretroviral-experienced patients were included in the MVC Expanded Access Program if they had an R5 screening result with Trof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 18 publications
4
62
2
1
Order By: Relevance
“…The coreceptor usage was determined from the V3 env region sequence by geno2pheno before the introduction of MVC (false-positive rate 10%). 4 The reverse transcriptase, protease, and integrase resistance mutations were interpreted with the last ANRS genotypic algorithm (www.hivfrenchresistance .org). According to the ANRS algorithm, the genotypic susceptibility score of treatment (GSS) of the MVC cotreatment received by the patient was calculated as follows: 1 for a sensitive drug and 0 for a resistant or possibly resistant drug.…”
Section: Virological Testingmentioning
confidence: 99%
“…The coreceptor usage was determined from the V3 env region sequence by geno2pheno before the introduction of MVC (false-positive rate 10%). 4 The reverse transcriptase, protease, and integrase resistance mutations were interpreted with the last ANRS genotypic algorithm (www.hivfrenchresistance .org). According to the ANRS algorithm, the genotypic susceptibility score of treatment (GSS) of the MVC cotreatment received by the patient was calculated as follows: 1 for a sensitive drug and 0 for a resistant or possibly resistant drug.…”
Section: Virological Testingmentioning
confidence: 99%
“…The V3 sequence permits a reliable viral tropism prediction, as shown in clinical studies [3][4][5][6][7][8][9] . In fact, genotypic determination is contemplated in the current European and German-Austrian guidelines 10 .…”
Section: Discussionmentioning
confidence: 99%
“…A study found integrase gene polymorphisms present in more than 10% of the 97 analyzed sequences (subtype B and non-B) from patients treated with RAL but these polymorphisms showed no impact on virological outcome either at week 24 or at week 48 (Charpentier et al, 2010). N155H, Q148H/R/K with G140S/A, and Y143R/C are the described mutational patterns that confer resistance to RAL, with or without secondary mutations (Garrido et al, 2010).…”
Section: Minor Mutationsmentioning
confidence: 99%
“…In general, the enhanced sensitivity Trofile (ESTA) assay (phenotypic assay) and V3 population genotyping are the recommended methods. A multicenter prospective study evaluated the performance of genotypic algorithms for prediction of HIV-1 coreceptor usage in comparison with a phenotypic assay for the determination of coreceptor usage (Recordon-Pinson et al, 2010). Researchers reported important differences between 13 algorithms in the sensitivity of detection of X4 isolates.…”
Section: Impact Of Hiv-1 Diversity In the Performance Of Genotypic Anmentioning
confidence: 99%